Spectrophotometric Determination of Escitalopram Oxalate in Bulk and Pharmaceutical Formulations Using 7,7,8,8-Tetracyanoquinodimethane - A. Al-Tamimi, Salma; A. Aly, Fatma; M. Al-Otaibi, Ohoud (Asian Journal of Chemistry, 2012)
The present work describes a simple and sensitive charge transfer spectrophotometric method for the determination of escitalopram oxalate in bulk and in its pharmaceutical preparations using 7,7,8,8-tetracyanoquinodimethane (TCNQ). The method is based upon a charge transfer of n-electrons from the donor moiety (7,7,8,8-tetracyanoquinodimethane) to the acceptor moiety (escitalopram). The spectrophotometric measurements were recorded by measuring the absorbance at 845 nm. The different experimental parameters were carefully studied to determine the optimal conditions for the assay procedure. Then, the method was used for the determination of escitalopram oxalate over the concentration range 4-20 μg/mL. The method was successfully applied for the determination of escitalopram oxalate in its tablets. The proposed method was compared with the reference method and was found to be equally accurate and precise.